2019
DOI: 10.3803/enm.2019.34.2.106
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucagon-Like Peptide 1 Receptor Agonists and Sodium-Glucose Cotransporter 2 Inhibitors in Reducing Cardiovascular Events in Patients with Type 2 Diabetes

Abstract: The prevalence of type 2 diabetes mellitus (T2DM), which is associated with cardiovascular morbidity and mortality, is increasing worldwide. Although there have been advances in diabetes treatments that reduce microvascular complications (nephropathy, neuropathy, retinopathy), many clinical studies have found that conventional oral hypoglycemic agents and glucose control alone failed to reduce cardiovascular disease. Thus, incretin-based therapies including glucagon-like peptide 1 (GLP-1) receptor agonists (RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…In addition, GLP-1 agonists increase natriuresis [17], reduce blood pressure, reduce inflammation, reduce ischemic injury, increase heart rate, increase plaque stabilization and decrease smooth muscle proliferation. It has been suggested that the positive effects of GLP-1 agonists on cardiovascular disease may be the result of a direct action on the arteriosclerotic process [66]. All these processes may leave an imprint on GLP-1 agonists' role in the improvement of ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GLP-1 agonists increase natriuresis [17], reduce blood pressure, reduce inflammation, reduce ischemic injury, increase heart rate, increase plaque stabilization and decrease smooth muscle proliferation. It has been suggested that the positive effects of GLP-1 agonists on cardiovascular disease may be the result of a direct action on the arteriosclerotic process [66]. All these processes may leave an imprint on GLP-1 agonists' role in the improvement of ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, SGLT-2 inhibitors could significantly reduce E/e′ and improve diastolic function of the left ventricle. Some studies suggested that SGLT-2 inhibitors could reduce oxidative stress [66], thereby improving arteriosclerosis and endothelial dysfunction. Experimental data in obese and diabetic mice demonstrated that the SGLT-2 inhibitor empagliflozin significantly ameliorated cardiac fibrosis, coronary arterial thickening, and cardiac macrophage infiltration, suggesting a direct cardiac effect along with an attenuation of oxidative stress on the myocardium [67].…”
Section: Discussionmentioning
confidence: 99%
“…78 In addition to a glucose-lowering effect, SGLT2 inhibitors exert several cardiorenal and metabolic benefits, including weight loss; therefore, they are thought to be promising therapeutic agents for patients with NAFLD. 79 Although beneficial effects continue to be reported, SGLT2 inhibitors are not yet generally recommended for the treatment of NAFLD.…”
Section: Sodium-glucose Cotransporter 2 (Sglt2) Inhibitorsmentioning
confidence: 99%
“…Nevertheless, warnings about HF risk have been added to the labels of several DPP-4is, including saxagliptin [124], alogliptin [26], and vildagliptin [125]. In contrast, other therapies, particularly GLP-1 receptor agonists (e.g., semaglutide and liraglutide) and SGLT2is (e.g., canagliflozin and empagliflozin), appear to have protective effects against CV disease [126].…”
Section: Risk Evaluationmentioning
confidence: 99%